The Effect Of Return On Assets (ROA), Net Profit Margin (NPM), Dividend Payout Ratio (DPR) And Dividend Yield (DY) On Stock Prices In The Subsectors Insurance Company Listed In Indonesia Stock Exchange Period 2015-2018 - Bustani Bustani (Yayasan Ilomata, 2020)
This study aims to examine the effect of Return on Assets (ROA), Net Profit Margin (NPM), Dividend Payout Ratio (DPR), Dividend Yield (DY) on Share Prices in Insurance sub-sector companies listed on the Indonesia Stock Exchange period 2015- 2018. This type of research is explanatory research. This study took a population of 16 companies with a sample of 10 companies selected through purposive sampling, so the number of sample observations over 4 years to 40 companies. The data used are secondary data, namely financial statement data in the form of ROA, NPM, DPR and DY ratios from 2015-2018. Secondary data was collected through documentation of research objects obtained by the IDX. Furthermore, the data were analyzed using multiple linear regression which had previously been fulfilled the classic assumption test as a prerequisite for conducting a regression test. The results of this study ROA and NPM significantly influence stock prices. DPR and DY have no effect on stock prices. The coefficient of determination (R2)worth of 0.29%, which means that the ROA, NPM, Parliament and DY explain the effect on stock prices by 29%, while the value of 71% is influenced by other variables not included in this study.